Gamma band functional connectivity reduction in patients with amnestic mild cognitive impairment and epileptiform activity. Issue 2 (3rd February 2022) - Cuesta, Pablo; Ochoa-Urrea, Manuela; Funke, Michael; Hasan, Omar; Zhu, Ping; Marcos, Alberto; López, Maria Eugenia; Schulz, Paul E.; Lhatoo, Samden; Pantazis, Dimitrios; Mosher, John C.; Maestu, Fernando
Abstract: There is growing evidence for neuronal hyperexcitability in Alzheimer's disease. Hyperexcitability is associated with an increase in epileptiform activity and the disruption of inhibitory activity of interneurons. Interneurons fire at a high rate and are frequently associated with high-frequency oscillations in the gamma frequency band (30–150 Hz). It is unclear how hyperexcitability affects the organization of functional brain networks. A sample of 63 amnestic mild cognitive impairment patients underwent a magnetoencephalography resting-state recording with eyes closed. Twenty (31.75%) mild cognitive impairment patients had epileptiform activity. A cluster-based analysis of the magnetoencephalography functional connectivity revealed a region within the right temporal cortex whose global connectivity in the gamma frequency band was significantly reduced in patients with epileptiform activity relative to those without epileptiform activity. A subsequent seed-based analysis showed that this was largely due to weaker gamma band connectivity of this region with ipsilateral frontal and medial regions, and the upper precuneus area. In addition, this reduced functional connectivity was associated with higher grey matter atrophy across several cortical regions in the patients with epileptiform activity. These functional network disruptions and changes in brain physiology and morphology have important clinical implications as they may contribute to cognitive decline in mild cognitive impairment and Alzheimer's disease. Abstract : Cuesta et al . report that epileptiform activity in magnetoencephalography data of patients with mild cognitive impairment is linked to reduced gamma band functional connectivity of the right temporal cortex with the rest of the brain. This reduced connectivity was associated with grey matter atrophy across several cortical regions. Graphical Abstract: Graphical Abstract